Pengaruh Kebijakan Moneter Dan Fiskal Terhadap Pengelolaan Portofolio Di Pasar Modal Indonesia (Study Kasus Pada Bank Indonesia) - Ramadhanti, Nouva Ayu; Kurniawati, Aprilia Tri; Pandin, Maria Yovita R. (CV. ITTC INDONESIA, 2024)
Monetary and fiscal policies are crucial tools for stabilizing and promoting growth within a country. In Indonesia, these policies are implemented and driven by Bank Indonesia. The purpose of this study is to determine how monetary and fiscal control impacts portfolio management in Indonesia’s capital market. The results of the study indicate that all independent variables (monetary policy and fiscal policy) have a significant effect on the dependent variable (portfolio management), both individually (partial significance) and collectively (simultaneous significance).